Parental and peer attachments, and psychological well-being as predictors of academic engagement among college students in Malaysia - Puteri Azlian Megat Ramli (Kulliyyah of Education, International islamic University Malaysia, 2017)
The present study examined the hypothesized structural relationships between parental attachment and peer attachment on academic engagement directly and indirectly through psychological well-being. A cross-sectional study utilizing survey method, the present study examined parental attachment, peer attachment, psychological well-being and academic engagement via instruments, which were adapted from a number of established measures. A total of 404 students (selected via proportionate random sampling) from students of International Islamic College Malaysia (IIC) who attended the usrah (Islamic awareness program which is a college compulsory course) session. The psychometric properties of the instruments were assessed through reliability analysis, exploratory and confirmatory factor analysis. Through the various analysis conducted, the instrument used in the present study is valid to be used in the local educational settings. Utilizing Structural Equation Modeling via AMOS version 21, the structural model was tested against the data for its fitness. Results indicated that psychological well-being did serve as plausible mediators in the relationships between support factors (parental attachment and peer attachment) and academic engagement. Specifically, psychological well-being emerged as one salient predictor in the indirect relationships between the support factors and academic engagement. Peer attachment and psychological well-being were the variables that had a direct association with academic engagement. In addition to the preceding findings, results also indicated that parental attachment did not directly influence academic engagement. Apparently, academic engagement is influenced by the psychological well-being that mediate the effect of parental attachment and peer attachment; therefore, those factors are the predictors of academic engagement based on flow theory, actualization theory, attachment theory and self-determination theory. Lastly, theoretical as well as practical implications of the study are also discussed.